Neural Mechanisms of Visual Working Memory in Prefrontal Cortex of the Macaque - Miller, Earl K. (J Neurosci, 1996)
Prefrontal (PF) cells were studied in monkeys performing a delayed matching to sample task, which requires working memory. The stimuli were complex visual patterns and to solve the task, the monkeys had to discriminate among the stimuli, maintain a memory of the sample stimulus during the delay periods, and evaluate whether a test stimulus matched the sample presented earlier in the trial. PF cells have properties consistent with a role in all three of these operations. Approximately 25% of the cells responded selectively to different visual stimuli. Half of the cells showed heightened activity during the delay after the sample and, for many of these cells, the magnitude of delay activity was selective for different samples. Finally, more than half of the cells responded differently to the test stimuli depending on whether they matched the sample. Because inferior temporal (IT) cortex also is important for working memory, we compared PF cells with IT cells studied in the same task. Compared with IT cortex, PF responses were less often stimulus-selective but conveyed more information about whether a given test stimulus was a match to the sample. Furthermore, sample-selective delay activity in PF cortex was maintained throughout the trial even when other test stimuli intervened during the delay, whereas delay activity in IT cortex was disrupted by intervening stimuli. The results suggest that PF cortex plays a primary role in working memory tasks and may be a source of feedback inputs to IT cortex, biasing activity in favor of behaviorally relevant stimuli.